Atuação da imprensa campo-grandense frente à desinformação: uma análise de conteúdo comparativo entre os jornais Correio do Estado e Campo Grande News - CAMILA ANDRADE ZANIN (2024)
This research aims to understand how local journalism positions itself in the face of the phenomenon of disinformation based on the analysis of the content of journalistic articles published in the online newspapers Correio do Estado and Campo Grande News, located in the municipality of Campo Grande, Mato Grosso do Sul. The keyword “disinformation” was used to collect all journalistic texts published on the two portals in the years 2020, 2021, 2022 and 2023, with 89 published in Correio do Estado and 183 in Campo Grande News, forming a corpus consisting of 272 analyzed journalistic texts. The material generated data from different vehicles that were compared to each other. Among the results found, it was observed that the subject is treated differently in the newspapers analyzed. Correio do Estado has a stance towards disinformation focused mainly on national politics, but it does little to explore the topic of disinformation, with a superficial approach, in addition to outsourcing the factchecking work (Project Comprova partnership). On the other hand, Campo Grande News presents an incisive stance towards the phenomenon, as it investigates local events involving the issue, publicizes local initiatives to combat it, addresses various topics (health, politics, education, culture, technology) and publishes texts of media education. They were found in both informative and opinionated formats of journalism.